Modeling and analysis of piezoelectric cantilever-pendulum system for multi-directional energy harvesting. (February 2017) - Xu, Jiawen; Tang, Jiong
Piezoelectric cantilevers are widely used in vibration energy harvesting. Simple cantilever-based harvesters are mostly unidirectional. In this article, we develop a cantilever-pendulum system that can harvest vibratory energy of excitations from an arbitrary direction. The new design consists of a traditional piezoelectric cantilever with a pendulum attached to the tip. It is shown analytically and experimentally that with proper parametric combination this system can induce modal energy interchange between beam vibration and pendulum motions due to 1:2 internal resonance, which ultimately yields multi-directional energy harvesting by a single cantilever. The underlying mechanisms of this design are analyzed in detail.